Nearest level control technique for three-phase transistor clamped H-bridge multilevel inverter - Hossain, Md Showkot; Hossain, Md Israfil; Mohd Said, Nurul Ain; Abd. Halim, Wahidah; Mohd Azam, Sazuan Nazrah; Hossain, Md Hasnat (IEEE, 2022)
Transistor Clamped h-bridge inverter is a new topology that can be found in the literature. The development of this inverter is based on the classical CHB multilevel inverter. However, all previously published modulation techniques are based on either the carrier-based PWM or SVPWM. Consequently, this paper proposed a nearest level control technique developed based on the round technique as it employs the nearest voltage level. To fully understand how the nearest level control technique works, the 13-level TCHB will be developed and analyzed in this research. The nearest level control technique is used to achieve better output quality. Several modulation index values are considered to validate this modulation technique's effectiveness. Simulation results establish the merits of the modulation technique. The results prove that this modulation technique can minimize the total harmonic distortion.